Captopril prevents the oxidative damage to proteins after renal ischemia reperfusion injury: Role of endothelin-1 - (:unkn) unknown (ELSEVIER SCI LTD, 1997)
Ischemia reperfusion (I/R) injury is one of the leading causes of the transplanted organ loss. In this experimental study, we investigated the effect of captopril on endothelin and eicosanoid release in I/R injury of the kidney. Rats were subjected to 60 min ischemia and 60 min of reperfusion of the left kidney in control and captopril groups. Tissue protein oxidation products, PGE(2) and LTB4 levels and plasma endothelin-l (ET-I) like activity were determined in sham operated, control and captopril groups. There were no differences in the LTB, levels among the groups. ET-1 and PGE(2), levels and protein oxidation products increased in the control group when compared with the sham. Captopril further increased both PGE(2) and ET-l concentrations and prevented protein oxidation. The increased Ei-l concentrations in the captopril treated group may imply the protective role of endothelin as the significant increase in protein oxidation products was reversed by captopril infusion. This has led us to believe that captopril might be useful in preventing I/R injury of the kidney. Also the release of endothelin from the vascular endothelium is increased by captopril and may be mediated by PGE(2).
Keywords: MOLECULAR CHARACTERIZATION; INTESTINAL ISCHEMIA; ILOPROST ZK-36374; FREE-RADICALS; GUINEA-PIG; RECEPTORS; RELEASE; MODEL; VERAPAMIL